Comparative study of switching strategies for cascaded H-bridge multilevel inverter - Usman Bashir Tayab (School of Electrical Systems Engineering, Universiti Malaysia Perlis, 2014)
In this project, four switching angle arrangement techniques are applied to a cascaded H-bridge multilevel inverter. The performance of 3-, 5-, 7-, 9-, 11-, 13- and 15-level cascaded H-bridge multilevel inverter with four switching angle arrangement techniques at different power factor loads have been evaluated and compared by using PSIM software.